Characterization of immune response and duration of protection in buffaloes immunized with haemorrhagic septicaemia vaccines - Chandrasekaran, S.; Kennett, L.; Yeap, P.C.; Muniandy, N.; Rani, B.; Mukkur, T.K.S. (Elsevier, 1994)
Two of the three buffaloes immunized with a non-adjuvanted broth bacterin were found to be protected against experimental challenge at 6 weeks but not at 3 months post-challenge. Similarly all buffaloes (4/4) immunized with alum-precipitated vaccine were protected at 6 months but only 1 of the 2 vaccinated animals were protected at 12 months post-immunization. On the other hand, buffaloes immunized with an oil adjuvant and a double emulsion vaccine were completely protected at 12 months post-immunization. Statistically significant differences between immunized versus non-immune animals became evident at 3 months post-immunization, although analysis of cumulative antibody titres of pre-challenge sera of vaccinated buffaloes surviving versus those succumbing to experimental challenge revealed significant by higher antibody titres in the former as compared to the latter group. These results suggested that there was a relationship between ELISA antibody titres and active protection in buffaloes. There also appeared to be a relationship between cutaneous delayed-type hypersensitivity and active protection in buffaloes. Preliminary analysis of the antibody isotype distribution in the pre-challenge sera of 2 buffaloes vaccinated with the oil adjuvant vaccine revealed predominance of IgG1 and IgG2 subclasses whose role in protection against haemorrhagic septicaemia was not eludicated.